¿Criminalización de la pobreza o criminalización a secas? - Finkelstein Nappi, Juan Lucas (2004)
Fil: Finkelstein Nappi, Juan Lucas. Universidad de Buenos Aires. Facultad de Derecho. Buenos Aires, Argentina